Soluble α-Klotho Serum Levels in Chronic Kidney Disease - Silverio Rotondi; Marzia Pasquali; Lida Tartaglione; Maria Luisa Muci; Giusy Mandanici; Cristiana Leonangeli; Silvia Sales; Alessio Farcomeni; Sandro Mazzaferro (International Journal of Endocrinology, 2015)
Transmembrane α-Klotho (TM-Klotho), expressed in renal tubules, is a cofactor for FGF23-receptor. Circulating soluble-α-Klotho (s-Klotho) results from TM-Klotho shedding and acts on Phosphate (P) and Calcium (Ca) tubular transport. Decreased TM-Klotho, described in experimental chronic kidney disease (CKD), prevents actions of FGF23 and lessens circulating s-Klotho. Thus, levels of s-Klotho could represent a marker of CKD-MBD. To evaluate the clinical significance of s-Klotho in CKD we assayed serum s-Klotho and serum FGF23 in 68 patients (age 58±15; eGFR 45±21 mL/min). s-Klotho was lower than normal (519±183 versus 845±330 pg/mL, P<.0001) in renal patients and its reduction was detectable since CKD stage 2 (P<.01). s-Klotho correlated positively with eGFR and serum calcium (Cas) and negatively with serum phosphate (Ps), PTH and FGF23. FGF23 was higher than normal (73±51 versus 36±11, P<.0002) with significantly increased levels since CKD stage 2 (P<.001). Our data indicate a negative effect of renal disease on circulating s-Klotho starting very early in CKD. Assuming that s-Klotho mirrors TM-Klotho synthesis, low circulating s-Klotho seems to reflect the ensuing of tubular resistance to FGF23, which, accordingly, is increased. We endorse s-Klotho as an early marker of CKD-MBD.